Future Fertility of Patients With No Embryo Transfer in Their First IVF Cycle Attempts - Zhu, Xuli; Cao, Mingya; Yao, Zhaohui; Lu, Peiyang; Xu, Yueming; Hao, Guimin; Zhao, Zhiming (Frontiers in Endocrinology, 2022)
Objective We aimed to evaluate the future outcomes of patients undergoing their first IVF (in vitro fertilization) attempt with no oocyte retrieved, no normal zygotes formed, or no embryos available for transfer and to identify factors affecting the live birth rate. Methods Patients who underwent no transplantable embryo in their first IVF cycles but carried out several consecutive cycles between January 2012 to December 2020 were retrospectively enrolled and divided into three groups:group A (no egg retrieval), group B (no normal zygotes formed), and group C (no embryos available to transfer). The patients were also divided into the live birth group and non-live birth group according to whether they got a live baby or not. The clinical data and the cumulative clinical outcomes of groups were compared. Results 496 patients met the inclusion criteria and enrolled, with 121 patients with no oocytes retrieved in group A, 138 patients with no normal zygotes formed in group B, and 237 patients with no embryos available to transfer in group C. The age [(34.75(5.82) vs 31.91(5.31), P<0.001; 34.75(5.82) vs 32.25(5.72), P<0.001)] and baseline FSH level [(13.04(8.82) vs 10.52(7.39), P=0.005; 13.04(8.82) vs 9.91(5.95), P<0.001)] of women in group A were significantly higher than those in groups B and C. The stable cumulative live birth rate/patient of three groups achieved 18.18% (after 5 cycles, group A), 28.98% (after 3 cycles, group B) and 20.25% (after 7 cycles, group C). Moreover, the multivariate regression analysis showed that female age and basic FSH were main factors affecting live birth outcome of patients with no embryo transfer in their first IVF cycle attempts. Conclusions The future clinical outcome may be better in women with no normal zygotes than those with no oocyte retrieved or no available embryo at their first IVF cycle attempts. The main factors influencing the live birth are age and ovarian reserve.